Interlanguage Errors In Descriptive Text Made By The Eight Gradestudents Of SMP Muhammadiyah 4 Sambi - Rafaidah, Anna, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M.Pd (2014)
This study aims at describing the interlanguage errors in descriptive text made by the eight grade students of SMP muhammadiyah 4 Sambi; identify the types of morphological errors, syntactical errors and discourse errors; describing the frequency of each type of errors; explain the dominant type of error; and identify the source of error. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation technique and documentation.The data will be analyzed using error analysis theory based on surface taxonomy strategy and linguistic category taxonomy by James (1998). There are four steps to collect data, namely: the writer gets the data of English made by the students from the teacher, the writer classifies all of the erroneous sentences of the student's composition based on the type of errors, the writer writes all the erroneous sentences into a list and used them as the data. The collected data are analyzed by using Selinker interlanguage theory, Carl James, Brown, and Corder the notion of errors, Dulay, Burt and Krashen classification of errors theory, Brown, Norrish, and Richard source of errors theory. The results of the research show that the eight grade students of SMP Muhammadiyah 4 Sambi still make 238 errors in their compositions. The writer finds that from 90 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. There are morphological 32,35% which covers: The error is classified into five errors. Indefinite and definite article 4,62%,bound morpheme 4,20%, wrong spelling 20,58 %, code switching 1,68%, and false friend or 1,26%. Errors on syntactical errors consist of 49,15% of errors covering: phrase 1, 68%, the use of verb tense 26,47%, Pronoun 7,98 %, Literal translation 1,68%, Conjunction1,68%, article 7,14% , simple preposition 1,26% of and errors on discourse consist of discourse error13,86% It divided into two parts, they are generic structure 12,60% and component of discourse 1,26%. The dominant of errors that the researcher found is in wrong spelling in morphological error with total number of errors are 49 errors or 20,58% of errors. The researcher also finds 2 dominant sources error, namely: interlingual transfer (7 errors or 2,94%) and intralingual transfer (9 errors or 3,78%).